Prevalence of Uncontrolled Type 2 Diabetes Mellitus And Its Associated Factors Among People Within Southern Part of Bangladesh - Akter, Farhana; Alam, S M Murshid Ul; Hasan, Md Mahbub; Rana, Md Mashud; Chowdhury, Nowshad Asgar; Karim, Masud; Mannan, Adnan (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Diabetes is a disorder which is very much related to a quality of lifestyle. Bangladesh is one of the countries having highest number of diabetes patients. Most of the population in this country used to take high glycemic indexed foods. In this study, we aimed to evaluate the quality of life of diabetic patients of the southern part and Chattogram city to investigate how controlled and uncontrolled diabetes is related to their lifestyle and socio-economic factors. Materials and methods: A multi-center, crosssectional study, conducted in five centers of Chattogram, in 2018-2019, registered 1,888 type 2 DM participants, tested for HbA1c and interviewed face-to-face for other information. Logistic regression analysis was conducted to identify factors associated with UDM. Descriptive analysis and chi square test were done to see the statistical significance between various parameters. Results: Among the study population nearly 72% were uncontrolled diabetes patients. The prevalence of uncontrolled diabetes in age <60 years was highly significant. Number of female uncontrolled diabetes patients were significantly higher. People having low income and lower level of education were more prone to uncontrolled diabetes. Conclusion: Health workers at the diabetic hospitals should intensify education and counselling of diabetics. Modifiable risk factors such as education, food and physical activity be considered as potential targets of interventions in southern part of Bangladesh. JCMCTA 2019 ; 30 (2) : 92-98